Bone morphogenetic proteins and other growth factors - Mastrocinque, Sandra (2004)
Complex fractures difficult to treat are still a challenge in Human Medicine and Veterinary Medicine. The surgical procedures involving the grafts may offer satisfactory results, but they increase surgical time and risk, besides the probability of complications. The use of bone morphogenetic proteins and other growth factors in systemic or local way may contribute to healing fractures, since it reduces healing time and complications.